Tracer the Future: A Study of Graduates and User Perceptionsin Arabic Language Education - Aina Salsabila; J. Nurhawani (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2025)
This tracer study and user survey aims to obtain information about the distribution of PBA graduate profiles, user responses to graduate competencies and what development needs to be done by PBA IAIN Lhokseumawe study program to produce better graduates in the future. This research uses a quantitative approach with survey methods. The collection of research data was carried out by distributing questionnaires and the data was analyzed by quantitative descriptive analysis. The survey subjects are PBA graduate amounting to 360 graduates, while the number of respondents tracked was around 135 respondents (37.5%) of the total graduates. And for the user survey, the subjects are who can be well connected as user graduate. The results of this study are: (a) The number of graduates who have worked is 114 respondents from the number tracked, mostly become teachers/education staff in schools and they are satisfied with their work. The waiting time to get a job in the time span before graduating is up to 1 year. While the average salary / month ranges from <1 - 3 million/month. (b) User response stated that they have the suitability of competence and level of competence of graduates is good and relevant to the needs of the world of education: (c) Development efforts that need to be carried out by PBA Study Program to produce superior graduates, namely, improving facilities and infrastructure as well as the quality of the learning process, holding activities that increase student knowledge, updating courses in accordance with the applicable curriculum and market needs and improve soft skills development and cooperation in the implementation of education, research and service at the local, national and international levels.